Agglomeration, Inequality and Economic Growth: Cross-section and panel data analysis - David Castells; Vicente Royuela (European Regional Science Association (ERSA), 2012)
The effects of inequality on economic growth depend on several factors. On one hand, they depend on the time horizon considered, on the initial level of income and on its initial distribution. But, on the other hand, as growth and inequality are also uneven across space, it also seems relevant to wonder about the effects of the geographic agglomeration of economic activity. Moreover, it seems relevant to consider not only the levels of inequality and agglomeration, but also their change -their evolution within countries- and the interaction between both processes. By considering different econometric specifications and introducing different measures for agglomeration at country level, especially urbanization and urban concentration rates, this work analyzes how increasing inequality and increasing agglomeration influence economic growth depending on the level of development and on the initial distribution of income. Our results suggest that while high inequality levels are a limiting factor for long-run growth -consistent with previous literature-, increasing inequality and increasing agglomeration have the potential to enhance growth in low-income countries where income distribution remains relatively equal, but can degenerate in congestion diseconomies in high-income ones, especially if income distribution becomes too unequal. The policy implications differ according to the level of development. For low-income countries, on one hand it has been argued that these countries should pursue growth first and then, just when growth is secured, attend distributional aspects; the recurrently argued trade-off between efficiency and equity in economics. This acknowledges the empirical fact that growth is by nature, and at least in the short-run, uneven. This unevenness is crucially spatial too; associated to the geographic concentration of economic activity (WDR 2009). On the other hand, however, it seems also quite clear that inequality becomes, sooner or later, a handicap for growth; developing countries that face high income inequalities are indeed also facing greater obstacles to achieve sustained long-run economic growth. Both facts together mean that while achieving higher economic growth may imply higher inequality due to higher geographic concentration of economic activity in the short-run, it also implies efforts for better income distribution in the long-run as a reinforcing, instead of confronting, objective to economic growth. For high-income countries congestion diseconomies seem to be a relevant issue to be addressed. A more balanced urban system, where small to medium size cities play a fundamental role, seem to be a better strategy than intense urban concentration (OCDE 2009). Finally, the fact that the benefits from agglomeration seem to depend on income distribution is likely to be signaling the relevance of good institutions in the process of development, in particular in what relates to economic geography. Surely the topic deserves more analysis and further research.
Keywords: 330